Evaluating Technology Acceptance and Service Quality: An Integrated TAM – TPB Approach In Digital Aplication Adoption - Ulfanianatul Hasanah; Siti Masrohatin; Khamdan Rifa'i (Eastasouth Institute, 2026)
The rapid expansion of digital payment applications has transformed financial transactions, particularly among university students who are highly engaged in digital ecosystems. Understanding the factors that drive adoption and shape perceptions of service quality is essential for both theory and practice. This study aimed to evaluate the adoption of digital payment applications by integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) to explain their combined effects on perceived service quality. A quantitative research design was applied using a cross-sectional survey distributed to 250 students in East Java who had experience using digital payment applications. The instrument employed a structured questionnaire measured on a five-point Likert scale, and data were analyzed using multiple regression techniques. The results revealed that perceived usefulness and attitude were the strongest predictors of perceived service quality, while perceived ease of use, subjective norms, and perceived behavioral control also contributed significantly, albeit with weaker effects. The integrated TAM–TPB model explained 57% of the variance in service quality, demonstrating a stronger explanatory power than either model alone. These findings suggest that both functional and psychosocial factors are critical in evaluating digital payment services. The study contributes theoretically by extending adoption models to the domain of service quality and provides practical insights for developers and policymakers to improve digital financial services for students.